A Chemical View on X‐ray Photoelectron Spectroscopy: the ESCA Molecule and Surface‐to‐Bulk XPS Shifts. Issue 2 (21st December 2017) - Delesma, Francisco A.; Van den Bossche, Maxime; Grönbeck, Henrik; Calaminici, Patrizia; Köster, Andreas M.; Pettersson, Lars G. M.
Abstract: In this paper we remind the reader of a simple, intuitive picture of chemical shifts in X‐ray photoelectron spectroscopy (XPS) as the difference in chemical bonding between the probed atom and its neighbor to the right in the periodic table, the so called Z+1 approximation. We use the classical ESCA molecule, ethyl trifluoroacetate, and 4 d ‐transition metals to explicitly demonstrate agreement between core‐level shifts computed as differences between final core‐hole states and the approach where each core‐ionized atom is replaced by a Z+1 atom. In this final state, or total energy picture, the XPS shift arises due to the more or less unfavorable chemical bonding of the effective nitrogen in the carbon geometry for the ESCA molecule. Surface core level shifts in metals are determined by whether the Z+1 atom as an alloy segregates to the surface or is more soluble in the bulk. As further illustration of this more chemical picture, we compare the geometry of C 1 s and O 1 s core‐ionized CO with that of, respectively, NO + and CF + . The scope is not to propose a new method to compute XPS shifts but rather to stress the validity of this simple interpretation. Abstract : ESCApe confusion : We emphasize the Z+1 approximation as an intuitive conceptual understanding of chemical shifts in electron spectroscopy. In this final‐state picture the shifts are due to differences in the chemical bonding when, e.g., carbon is replaced by nitrogen. We illustrate this with shifts and structure changes in molecules, surface core‐level shifts for transition metals, and core‐level shifts induced by oxygen adsorption on Pd(111) and Ag(111).